THE STUDIES ON DEMOGRAPHIC HISTORY ON PALESTINE DURING BRITISH ADMINISTRATION, 1917-1948: ISSUES AND CONCERNS - Zainal Abidin, Ummu Zainab Al-Abidah; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2013)
In the course of the history of Palestine, the years of 1917 until 1948 stood out as the time when it was briefly administered by the Imperial British, and became especially significance as the demography of the land was transferred from an Arab majority into a land dominated by the Jews. Various studies have been done this subject, and had centred on several issues that are integral to the understanding of how Israel was eventually formed in 1948. Therefore the purpose of this paper will be to identify the significance of demographic study on Palestine during the time it was administered by the British for 31 years. This paper will be divided into four parts. Firstly it will define the meaning of demographic study for Palestine for the purpose of identifying the borders and limitation of such studies, as well as the significance of such studies to broader study of Palestine in particular. Secondly, the authors will review several past studies which will be able to identify the concerns and issues of these studies and then elaborated in the third part, and the whole discussion will concluded in the final part. The authors have applied the use of historical method, by referring to primary and secondary sources.